2019
DOI: 10.1037/edu0000305
|View full text |Cite
|
Sign up to set email alerts
|

Does the track matter? A comparison of students’ achievement in different tracks.

Abstract: This study compared the effects of being in different tracks during the first three years of secondary education on student academic performance. A sample of a longitudinal cohort study in Flanders (3205 students in 46 schools) was used to describe the learning gains for mathematics and reading comprehension. Four tracks were distinguished, with a clear hierarchy in mean student academic ability. A comparison was made per pair of tracks that are hierarchically consecutive by matching students who are comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
(239 reference statements)
0
7
0
Order By: Relevance
“…Specifically, research on achievement gaps in secondary school mostly looked at between track differences in learning gains (e.g. Becker et al, 2014;Dockx, de Fraine, & Vandecandelaere, 2018;Kulik & Kulik, 1982;. In contrast, this paper will describe differences in academic growth between high achievers and their peers within the highest track of secondary school.…”
Section: Introductionmentioning
confidence: 96%
“…Specifically, research on achievement gaps in secondary school mostly looked at between track differences in learning gains (e.g. Becker et al, 2014;Dockx, de Fraine, & Vandecandelaere, 2018;Kulik & Kulik, 1982;. In contrast, this paper will describe differences in academic growth between high achievers and their peers within the highest track of secondary school.…”
Section: Introductionmentioning
confidence: 96%
“…The vocational track involves practical training and primarily has a labour-market orientation. Reading comprehension, self-concept, intrinsic motivation, interest, enjoyment, strategy knowledge and recreational reading frequency are demonstrated to be lower for students in the technical and especially in the vocational track (Dockx et al, 2019;Kozminsky & Kozminsky, 2001;Mol & Jolles, 2014;OECD, 2019b;Retelsdorf et al, 2011;Roeschl-Heils et al, 2003;Schaffner, Philipp, & Schiefele, 2016). These differences could result in differential relationships between students' motivational and behavioural characteristics on the one hand and their reading comprehension on the other hand.…”
Section: Differences Between Educational Tracksmentioning
confidence: 95%
“…Third, in many countries, secondary school students are divided between separate educational tracks. Recently, there has been growing interest in studying differences between these tracked groups (Dockx, De Fraine, & Vandecandelaere, 2019). However, research considering educational tracks in relation to the (respective) contribution of motivational and behavioural characteristics to reading comprehension remains very scarce.…”
Section: Problem Statementmentioning
confidence: 99%
“…Accordingly, studies show that students with lower academic abilities and disadvantageous socioeconomic backgrounds are placed in lower tracks, which negatively affect academic performance (Becker, Lüdtke, Trautwein, Köller, & Baumert, ; Guill, Lüdtke, & Köller, ; Gustafsson, ; Korthals & Dronkers, ; Retelsdorf, Becker, Köller, & Möller, ). Using the same sample as this study, a study in Flanders also found that lower track placement negatively affects academic performance (Dockx et al ., ). Therefore, increased inequality in academic performance is explained by the separation of student across lower and higher tracks, with lower track allocation negatively affecting academic performance.…”
Section: Introductionmentioning
confidence: 97%
“…A Flemish data set was used for describing the development of school engagement during the first 4 years of secondary education. The same data set was also used for studies on the effects of tracks on academic performance (Dockx, De Fraine, & Vandecandelaere, ) and academic self‐concept (Dockx, De Fraine, & Vandecandelaere, ). However, in this study a new year's data have been added.…”
Section: Introductionmentioning
confidence: 99%